Political Allegiance After European Integration - White, J. author. aut Link
XV, 266 p.
Keywords: How should political community be seen in the context of European integration? This book combines a theoretical treatment of political allegiance with a study of ordinary citizens, examining how taxi-drivers in Britain, Germany and the Czech Republic talk politics and situate themselves relative to political institutions and other citizens.